Cost-effective activated carbon (AC) production from partial substitution of coal with red mud (RM) as additive for SO2 and NOx abatement at low temperature. (1st June 2021) - Niu, Jian; Zhang, Huirong; Li, Linbo; Guo, Yanxia
Graphical abstract: Highlights: Utilization of red mud (RM) partial substitution of coal for AC production. RM addition enhanced SO2 removal and inhibited NO removal. The presence of SO2 promoted NO removal. Related mechanisms were proposed. Suggest an approach for waste RM's high-value utilization. Abstract: Red mud (RM) was used as additive for activated carbon (AC) production and the results show that RM could adjust its physiochemical texture and performance. RM promotes the development of AC's pore structure and surface chemistry. The as-derived granular 10RM/AC' surface area of micropore, total specific area, and total pore volume is up to 451 m 2 /g, 848 m 2 /g, 0.49 cm 3 /g, which are 11%, 49%, and 88% higher than AC, respectively. Meanwhile, O/C and π-π* group significantly increased with the addition of RM. RM's addition promotes desulfurization activity and lowers denitrification efficiency. 10RM/AC shows maximum sulfur capacity (65.1 mg/g), which is 17.9% higher than that of AC (55.2 mg/g). However, ACs' nitrate capacity has declined from 0.86 mg/g to 0.40 mg/g due to the poisoning effect of RM's high CaO/Na2 O content, etc. The presence of SO2 obviously promoted the nitrate capacity from 0.94 mg/g to 1.16 mg/g due to the new acid site's formation by sulfate species through SO2 and NH3 . Meanwhile, the inorganic components (Fe-, Ca- and Na-containing species) in ACs from RM catalyze SCR reaction and the related mechanism was proposed. The results of this research provided an approach and preliminary information for utilizing industrial waste RM for cost-effective AC preparation.